Food groups and risk of coronary heart disease, stroke and heart failure: A systematic review and dose-response meta-analysis of prospective studies - Bechthold, Angela; Boeing, Heiner; Schwedhelm, Carolina; Hoffmann, Georg; Knüppel, Sven; Iqbal, Khalid; De Henauw, Stefaan; Michels, Nathalie; Devleesschauwer, Brecht; Schlesinger, Sabrina; Schwingshackl, Lukas (Critical reviews in food science and nutrition, 2019)
Background: Despite growing evidence for food-based dietary patterns' potential to reduce cardiovascular disease risk, knowledge about the amounts of food associated with the greatest change in risk of specific cardiovascular outcomes and about the quality of meta-evidence is limited. Therefore, the aim of this meta-analysis was to synthesize the knowledge about the relation between intake of 12 major food groups (whole grains, refined grains, vegetables, fruits, nuts, legumes, eggs, dairy, fish, red meat, processed meat, and sugar-sweetened beverages [SSB]) and the risk of coronary heart disease (CHD), stroke and heart failure (HF). Methods: We conducted a systematic search in PubMed and Embase up to March 2017 for prospective studies. Summary risk ratios (RRs) and 95% confidence intervals (95% CI) were estimated using a random effects model for highest versus lowest intake categories, as well as for linear and non-linear relationships. Results: Overall, 123 reports were included in the meta-analyses. An inverse association was present for whole grains (RR CHD : 0.95 (95% CI: 0.92-0.98), RR HF : 0.96 (0.95-0.97)), vegetables and fruits (RR CHD : 0.97 (0.96-0.99), and 0.94 (0.90-0.97); RR stroke : 0.92 (0.86-0.98), and 0.90 (0.84-0.97)), nuts (RR CHD : 0.67 (0.43-1.05)), and fish consumption (RR CHD : 0.88 (0.79-0.99), RR stroke : 0.86 (0.75-0.99), and RR HF : 0.80 (0.67-0.95)), while a positive association was present for egg (RR HF : 1.16 (1.03-1.31)), red meat (RR CHD : 1.15 (1.08-1.23), RR stroke : 1.12 (1.06-1.17), RR HF : 1.08 (1.02-1.14)), processed meat (RR CHD : 1.27 (1.09-1.49), RR stroke : 1.17 (1.02-1.34), RR HF : 1.12 (1.05-1.19)), and SSB consumption (RR CHD : 1.17 (1.11-1.23), RR stroke : 1.07 (1.02-1.12), RR HF : 1.08 (1.05-1.12)) in the linear dose-response meta-analysis. There were clear indications for non-linear dose-response relationships between whole grains, fruits, nuts, dairy, and red meat and CHD. Conclusion: An optimal intake of whole grains, vegetables, fruits, nuts, legumes, dairy, fish, red and processed meat, eggs and SSB showed an important lower risk of CHD, stroke, and HF.